Feasibility to measure the properties of φ(1020) meson in collisions of bismuth nuclei at an energy of 9.2 GeV in the NICA collider using the MPD experimental setup - Berdnikov Yaroslav; Ivanishchev Dmitry; Kotov Dmitry; Malaev Mikhail; Riabov Andrei (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
We report results on a feasibility study of measuring the properties of φ (1020) resonance in collisions of bismuth nuclei at an energy of 9.2 GeV using the MPD detector at the NICA collider. Model calculations of heavy nuclei collisions and the secondary particles – the MPD material interaction have been performed for the φ(1020) → K+ + K– decay. The dependencies of the process’es key parameters on the transverse momentum for different intervals of centrality of bismuth nuclei collisions were obtained in the rapidity range from –0.5 to +0.5. The evaluations of the mass resolution, detection efficiency of the MPD detector and the transverse momentum spectra for the φ(1020) resonance were made. The sample size of bismuth nuclei collision data that allowed the φ(1020) resonance properties to be reconstructed with a sufficiently good accuracy to conduct a study of the φ(1020) meson production was estimated.